Addis Ababa Sidewalk Design and Maintenance Guidelines - World Bank (Washington, DC: World Bank, 2022)
Walking is a predominant mode of travel in Addis Ababa representing more than half of the daily trips. The mild climate in Addis Ababa is conducive for this healthy and green mode of transport. However, sidewalks are often narrow, uneven, obstructed, or non-existent, causing discomfort and road safety risks to the most vulnerable road users: pedestrians. Studies done by the WHO and the Government showed that AA has disproportionately high pedestrian fatalities. The study on Addis Ababa Sidewalk Safety and Improvement takes the approach of integrating digital technology and Urban Inventory in sidewalk surveys, applies the Global Walkability Index in sidewalk assessments, and adapts the global best practice to the local context. The Addis Ababa Sidewalk Design and Maintenance Guidelines seek to promote the development of quality pedestrian infrastructure and environments, based on the condition’s assessment and global best practices. The design specifications and visual rendering provide recommendations for the policy makers to consider when developing the City’s design and maintenance standards for urban roads, sidewalks, public spaces, and transit-oriented development, some of which are being carried out as part of the technical assistance program of the World-Bank financed Transport Systems Improvement Project (TRANSIP).